Eating habits and emotional welfare of engineering students at The Private University of Tacna during the compulsory immobilization due to COVID-19 - Cartagena Cutipa, Raul (2021)
The objective of the research was to estimate the relationship between changes in eating habits and emotional well-being of engineering college students at the Private University of Tacna during mandatory confinement due to COVID-19. The study was descriptive cross-sectional with a sample from 195 participants, two instruments were used; the psychometric scale of depression, anxiety and stress (DASS-21) and an instrument to measure eating habits that were validated by presenting an internal consistency value of α = 0.937 and 0.826 respectively. The variation in eating habits was evaluated using an instrument consisting of 19 items that diagnose whether the participant increased or decreased the consumption of healthy and unhealthy products. For the validation of the results, the DASS was adjusted by means of a confirmatory factor analysis that groups together the levels of stress, anxiety and depression that have a Comparative Adjustment Index (CFI) = 0.91; Root mean square error of approximation (RMSEA) = 0.78 and a Tucker Lewis index (TLI) = 0.90. The results indicate a tendency to consume less healthy foods which would cause a decrease in the consumption of healthier foods, which is significantly related to negative states of emotional health in which they show a high prevalence of stress (57.7%), anxiety (82 %) and depression (84.2%), being notably higher in female students with notably significant anxiety episodes. However, the limitations of the study, the direct and highly significant relationship between changes in eating habits and states of negative affection is notorious, which suggests implementing strategies that contribute to improving psychological health by developing interventions that are related to a healthier diet to improve the well-being of the university population.